1995
DOI: 10.3109/00365519509075377
|View full text |Cite
|
Sign up to set email alerts
|

The effect of n-3 fatty acids on neutrophil chemiluminescence

Abstract: The effect of dietary supplementation with n-3 polyunsaturated fatty acids (PUFAs) on the production of free oxygen radicals from activated neutrophils was investigated in healthy subjects, using chemiluminescence. In the first study 22 persons were give 4 g n-3 PUFAs daily for 6 weeks. There was a median reduction of chemiluminescence from neutrophils stimulated with opsonized zymosan of 37% (p < 0.001). The median content of eicosapentaenoic acid in platelets, used as an indicator for cellular fatty acid pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 25 publications
3
34
2
Order By: Relevance
“…Supplementation studies of fish oil have reported 30–50% decreases in the production of reactive oxygen species (superoxide or hydrogen peroxide) by stimulated human neutrophils,37 and human monocytes 38. These studies have used similar doses of fish oil to this study (3.1–8.4 g/day EPA plus DHA).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Supplementation studies of fish oil have reported 30–50% decreases in the production of reactive oxygen species (superoxide or hydrogen peroxide) by stimulated human neutrophils,37 and human monocytes 38. These studies have used similar doses of fish oil to this study (3.1–8.4 g/day EPA plus DHA).…”
Section: Discussionmentioning
confidence: 90%
“…Studies have shown that in sufficient quantities, dietary fish oil results in decreased leucocyte chemotaxis,36 decreased production of reactive oxygen species37 38 and proinflammatory cytokines,36 39 and decreased adhesion molecule expression40.…”
Section: Discussionmentioning
confidence: 99%
“…Although the effects of long-chain fatty acids (particularly the n-3 class of PUFA) on neutrophil functional parameters such as superoxide production and chemotaxis have been investigated extensively in numerous ex vivo studies [9][10][11][12][13][14], to our knowledge no studies have addressed adequately the effects of such fatty acids on neutrophil apoptosis. In the work presented here, retinoic acid (RA)-differentiated HL-60 cells were used as a model for human neutrophils.…”
Section: Introductionmentioning
confidence: 99%
“…have been shown to suppress production of reactive oxygen species (superoxide and hydrogen peroxide) in stimulated leukocytes. [48][49][50][51][52][53][54] Superoxide production was reduced in isolated human 52 and rat 54 polymorphonuclear leukocytes, as well as in human monocytes. 48,53 Other potential mechanisms may relate to the assembly of ω3 fatty acids in membrane lipids and lipoproteins making the double bonds less susceptible to free radical attack, 55 inhibition of the pro-oxidant enzyme phospholipase A 2 , 56 and stimulation of antioxidant enzymes.…”
mentioning
confidence: 97%